Pengaruh Media Pembelajaran Berbasis Flipbook terhadap Hasil Belajar IPAS di Kelas IV SDN 2 Kuanyar - Saputra, Nanda Eka; Zumrotun, Erna; Attalina, Syailin Nichla Choirin (Jurnal Simki Pedagogia, 2024)
The purpose of this study is to assess the impact of the utilization of flipbooks as a learning tool on the learning outcomes of students in class IV at SD Negeri 2 Kuanyar. especially regarding their understanding of the concept of plant reproduction 21 students participated in this study, which used a quantitative methodology and a pre-experimental design with a single group pre-and post-tests. Multiple-choice exams that were administered both before and after the learning therapy were used to gather data. Flipbook-based learning media was used to collect this data. According to the study's findings, class IV student learning outcomes at SD Negeri 2 Kuanyar significantly improved. Compared to the pretest score (60.38%) of 13.14%, the average posttest score was 73.52% higher. The results show that flipbook media as a learning tool has an influence on student learning outcomes, especially in understanding the concept of plant reproduction. This shows that the use of interactive learning media such as flipbooks can influence student engagement and understanding of science.